The Compliance of Local Self-Government Financing Rules in the Republic of Serbia and the Republic of Srpska with the European Charter of Local Self-Government - Hadži Stević, Brano (NBP. Nauka, bezbednosti, policija, 2025)
A necessary precondition for the existence and functioning of local self-government is the existence of appropriate financial resources. The European Charter of Local Self-Government is an important legal act regarding the question of local self-government in general, including its financing, since this act sets a number of standards that represent a common frame for national legislators. This paper tends to analyze the legislation of the Republic of Serbia and the Republic of Srpska concerning financing and its compliance with the principles from the Charter. In order to achieve this goal, dogmatic and comparative methods will be used, as well as statistical data. Upcoming analysis will show that the legislation in Serbia and Srpska is not in toto in accordance with the standards prescribed in the Charter regarding the financing of local self-government units.
Keywords: local self-government, the European Charter of Local Self-Government, financing, standards